Supply chain choice with financial constraints on the internet: Drop shipping vs. traditional channel. (November 2019) - Zeng, Kuan; Gong, Yeming (Yale); Xu, Xianhao
Highlights: Supply chain choice on internet first depends on the newsvendor critical fractile. Then, the supply chain choice rests on the retailer's preference and capital level. Retailers cannot obtain the trade credit unless their capital exceeds a threshold. Under the full trade credit type, wholesalers may decide the channel structure. Decision zones for the channel structures are found under each trade credit policy. Abstract: While some existing literature on e-commerce supply chains neglects financial constraints, this study analyzes channel choice on the internet between drop shipping and traditional channel in a supply chain including a wholesaler W and multiple financially constrained online retailers. Drop shipping is a new order fulfillment practice on the internet, wherein retailers focus on customer acquisition while forwarding orders to wholesalers. A traditional channel is another mode of operation that is widely used on the internet, where retailers own and handle inventory, while wholesalers extend credit conditioned on retailers' financial status. To understand the impact of a retailer's financial constraints on her supply chain structure on the internet, we formulate profit-maximizing inventory models for both wholesaler W and retailer R . By analyzing and comparing their expected payoffs under different channels, we find that the supply chain structure on the internet first depends on the critical fractile in a newsvendor setting, and subsequently it depends on R 's preference and capital level if the critical fractile of R is much larger than that of W . Furthermore, we discuss the choice of channel on the internet under different trade credit policies and find that W always provides two channel options conditionally under partial trade credit but may offer only one supply chain structure under full trade credit. Finally, we provide management insights by identifying the decision zones for different supply chain structures under full or partial trade credit on the internet.